Geographic Information System (GIS) Based Zakat Distribution Model for Optimizing Efficiency and Transparency in Zakat Management: Model Distribusi Zakat Berbasis Geographic Information System (GIS) Untuk Optimalisasi Efisiensi dan Transparansi Pengelolaan Zakat - Wahyudi, Muhamad; Rokhaniyah, Siti; 'Aini, Saras Shinta Qurrota; Hamdani, Rifki (Universitas Muhammadiyah Sidoarjo, 2025)
Zakat institutions in Indonesia still face various challenges, particularly in zakat management. One of the main issues is how to ensure zakat distribution is well-targeted, effective, and efficient. Determining the appropriate distribution areas becomes a solution in addressing zakat distribution problems. This study aims to design a web-based zakat distribution application by utilizing Geographic Information System (GIS) technology, integrated with SAGA GIS and QGIS tools, using a mixed-methods approach. Mapping of zakat recipients (mustahik) and prioritization of distribution areas were analyzed using spatial data. Meanwhile, field surveys were conducted to validate data accuracy. The study reveals that zakat distribution using geospatial technology is more effective and efficient compared to conventional methods. The developed web-based zakat distribution system application allows both zakat administrators and the public to monitor zakat distribution programs in real-time. These findings affirm that the application of geospatial technology can be a strategic solution to strengthen zakat governance based on the principles of maqashid sharia.